2007
DOI: 10.1016/j.jmaa.2007.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Generalized convexity and inequalities

Abstract: Let R + = (0, ∞) and let M be the family of all mean values of two numbers in R + (some examples are the arithmetic, geometric, and harmonic means). Given m 1 , m 2 ∈ M, we say that a function f :for all x, y ∈ R + . The usual convexity is the special case when both mean values are arithmetic means. We study the dependence of (m 1 , m 2 )-convexity on m 1 and m 2 and give sufficient conditions for (m 1 , m 2 )-convexity of functions defined by Maclaurin series. The criteria involve the Maclaurin coefficients. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
176
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(178 citation statements)
references
References 9 publications
2
176
0
Order By: Relevance
“…al. [1] and Iscan [5] have investigated various properties of harmonic convex functions. Noor and Noor [9] have shown that the minimum of the differentiable harmonic convex functions on the harmonic convex set can be characterized by a class of variational inequalities, which is called harmonic variational inequality.…”
Section: Introductionmentioning
confidence: 99%
“…al. [1] and Iscan [5] have investigated various properties of harmonic convex functions. Noor and Noor [9] have shown that the minimum of the differentiable harmonic convex functions on the harmonic convex set can be characterized by a class of variational inequalities, which is called harmonic variational inequality.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Anderson et al in [2] developed a systematic study to the classical theory of continuous and midconvex functions, by replacing a given mean instead of the arithmetic mean. for all x, y ∈ I and t ∈ [0, 1].…”
Section: Introductionmentioning
confidence: 99%
“…For useful details and generalization of Hermite-Hadamard inequalities, see [1,2,3,4,5,6,7,8]. The harmonic convex function, was introduced and studied by Anderson et al [9] and Iscan [1]. Iscan [3] introduced the concept of harmonic s-convex function in second sense.…”
Section: Introductionmentioning
confidence: 99%